Autonomous flying robots unmanned aerial vehicles and micro aerial vehicles - Nonami, Kenzo (Springer, 2010)
Worldwide demand for robotic aircraft such as unmanned aerial vehicles (UAVs) and micro aerial vehicles (MAVs) is surging. This book describes step by step the development of small or miniature unmanned aerial vehicles and discusses in detail the integrated prototypes developed at the robotics laboratory of Chiba University.